Hiligaynon Lessons - Motus, Cecile L. (PALI Language Texts-Philippines, 1971)
The Philippines series of the PALI Language Texts, under the general editorship of Howard P. McKaughan, consists of lesson textbooks, grammars, and dictionaries for seven major Filipino languages.